2012
DOI: 10.1016/j.crohns.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA in inflammatory bowel disease

Abstract: Our results suggest that several miRNAs could distinguish CD from UC by real-time PCR. This further highlights the putative role of miRNAs as contributors to IBD pathogenesis. They may help develop new non-invasive biomarkers to distinguish UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
160
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(180 citation statements)
references
References 24 publications
16
160
3
1
Order By: Relevance
“…miR-200b is expressed in a variety of cells and modulates key cellular functions, such as cell proliferation, motility, apoptosis, and stem cell properties, and it controls signals in angiogenesis and epithelial-mesenchymal transition, a process in which epithelial cells acquire mesenchymal characteristics (Brabletz and Brabletz 2010). Regulation of miR-200b/c modifies TLR4 signaling in macrophages, with effects on host innate defenses against periodontal pathogens (Wendlandt et al 2012), while miR-200c-5p was found to be increased in inflammatory bowel disease patients (Paraskevi et al 2012). There have been no studies reporting miR-200b expression in gingival tissue in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…miR-200b is expressed in a variety of cells and modulates key cellular functions, such as cell proliferation, motility, apoptosis, and stem cell properties, and it controls signals in angiogenesis and epithelial-mesenchymal transition, a process in which epithelial cells acquire mesenchymal characteristics (Brabletz and Brabletz 2010). Regulation of miR-200b/c modifies TLR4 signaling in macrophages, with effects on host innate defenses against periodontal pathogens (Wendlandt et al 2012), while miR-200c-5p was found to be increased in inflammatory bowel disease patients (Paraskevi et al 2012). There have been no studies reporting miR-200b expression in gingival tissue in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies in IBD, however, have been conflicting, as initial studies found dissimilar miRNA expression profiles compared with tissues, leading to the suggestion that peripheral blood miRNAs may reflect circulating leukocytes rather than expression in remote tissues. However, more recent investigations have been able to demonstrate several previously reported dysregulated tissue miRNAs with increased expression in peripheral blood [Paraskevi et al 2012;Yang et al 2013].…”
Section: Mirna General Overviewmentioning
confidence: 99%
“…Reduced levels of miR124 in colon tissues appear to increase the expression and activity of signal transducer and activator of transcription3, and this mediates the pathogenesis of UC in children [124] . miRNAs in peripheral blood: Paraskevi and colleagues [125] found that six miRNAs (miR16, miR21, miR285p, miR1515p, miR155, and miR199a 5p) were remarkably upregulated in blood from UC patients compared with healthy controls. miR155 had the highest expression level of these six UC associated miRNAs in peripheral blood.…”
Section: Mirnas In Ucmentioning
confidence: 99%
“…miRNAs in peripheral blood: Apart from assessing miRNA expressions in peripheral blood in UC, Paraskevi et al [125] examined miRNA expression patterns in peripheral blood samples from 128 patients with active CD and 162 healthy individuals. Eleven miRNAs (miR16, miR23a, miR29a, miR106a, miR107, miR126, miR191, miR199a5p, miR200c, miR 3623p, and miR5323p) were markedly upregulated in peripheral blood from CD patients as compared with healthy individuals.…”
Section: Mirnas In CDmentioning
confidence: 99%